2016
DOI: 10.1371/journal.pntd.0004782
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Yeast Derived Chikungunya Virus Like Particles (CHIK-VLPs) and Its Evaluation as a Potential Vaccine Candidate

Abstract: Chikungunya virus (CHIKV) has emerged as a global health concern due to its recent spread in both old and new world. So far, no CHIKV specific drug or vaccine is licensed for human use. In this study, we report production of Chikungunya virus like particles (CHIK-VLPs) using novel yeast expression system (Pichia pastoris) and its evaluation as vaccine candidate. The gene encoding structural polyprotein of CHIKV from a recent epidemic strain was cloned into yeast expression system. The multicopy integrants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 47 publications
1
37
0
3
Order By: Relevance
“…Moreover, they do not require chemical inactivation, as with viral lysate, reducing the risk of alterations of antigenic epitopes. Synthetic viruses are well characterized and have already been considered to be a powerful template to develop next‐generation vaccines . However, there are few references in the literature regarding the use of these antigens as diagnostic tools …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they do not require chemical inactivation, as with viral lysate, reducing the risk of alterations of antigenic epitopes. Synthetic viruses are well characterized and have already been considered to be a powerful template to develop next‐generation vaccines . However, there are few references in the literature regarding the use of these antigens as diagnostic tools …”
Section: Discussionmentioning
confidence: 99%
“…Synthetic viruses are well characterized and have already been considered to be a powerful template to develop next-generation vaccines. 47,[62][63][64] However, there are few references in the literature regarding the use of these antigens as diagnostic tools. 65,66 Interestingly, using MAC-ELISA, a very strong detection signal for It has previously been shown that the PAD sensitivity is generally lower than that for ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the ability of yeast to perform post-translational modifications, it represents a step forward in VLP production. Recently, Chikungunya VLPs were produced using P. pastoris and promising results were obtained in terms of murine immunisation [15]. Indeed, several yeast-produced VLPs have already reached approval by regulatory agencies, such as papillomavirus VLP [16].…”
Section: Bacteria and Yeastmentioning
confidence: 99%
“…Moreover, contamination with endotoxins is a critical consideration in manufacturing injectable vaccines because it can cause severe side effects such as septic shock and tissue damage (Magalhaes et al 2007). Studies have suggested that endotoxins can be removed effectively by treatment with Triton X-114 (Liu et al 1997;Schadlich et al 2009). Recently, moreover, it has been possible to enhance the solubility of target proteins and to use endotoxin-free E. coli cell lines (Sorensen and Mortensen 2005;Mamat et al 2015).…”
Section: Comparison Of Expression Systems For Producing Vlpsmentioning
confidence: 99%